Synthesis and Adsorption of Organo-Montmorillonite/Poly(Acrylic Acid) Superabsorbent Composite. Issue 1 (January 2013) - Zhu, Linhui; Zhang, Lili; Tang, Yaoji; Yang, Jing
Organo-montmorillonite /poly (acrylic acid) superabsorbent composite was prepared by intercalation polymerization of acrylic acid (AA) and organo-montmorillonite (OMMT). The composite was characterized by means of Fourier-transform spectroscopy (FTIR), scanning electron microscopy (SEM) and thermogravimetric analysis (TGA). Maximum absorbency of OMMT/PAA in distilled water and 0.9% NaCl was 1439 and 97 g/g, respectively. Water retention of the composite was also tested. The composite was used for removal of heavy metal ions from aqueous solutions. The maximum adsorption capacities for Pb 2+, Cu 2+ and Ni 2+ were 1006.97, 280.56 and 165.67 mg/g, respectively, and the adsorption was consistent with the Freundlich model. It was found that the superabsorbent composite showed good re-use performance in wastewater treatment.